2022
DOI: 10.1039/d1nr08429a
|View full text |Cite
|
Sign up to set email alerts
|

Triggering the nanophase separation of albumin through multivalent binding to glycogen for drug delivery in 2D and 3D multicellular constructs

Abstract: Engineered nanoparticles for encapsulation of bioactive agents hold promise to improve diseases diagnosis, prevention and therapy. To advance this field and enable the clinical translation, the rational design of nanoparticles...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…The unmodified PG NPs were effectively degraded by α ‐amylase to up to 90% within 24 h, whereas PG EDA NPs showed higher resistance to α ‐amylase digestion (30% degradation only) after a similar treatment (Figure 2c). In our earlier study, [ 17 ] the limited degradability displayed by amine‐functionalized glycogen NPs was attributed to the electrostatic repulsion between the cationic glycogen NPs and the positively charged enzymes (isoelectric point = 6.5–7). These results further confirm our hypothesis and suggest that PG EDA NPs are not readily degraded in biological environments containing α ‐amylase (i.e., blood, gastrointestinal tract).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The unmodified PG NPs were effectively degraded by α ‐amylase to up to 90% within 24 h, whereas PG EDA NPs showed higher resistance to α ‐amylase digestion (30% degradation only) after a similar treatment (Figure 2c). In our earlier study, [ 17 ] the limited degradability displayed by amine‐functionalized glycogen NPs was attributed to the electrostatic repulsion between the cationic glycogen NPs and the positively charged enzymes (isoelectric point = 6.5–7). These results further confirm our hypothesis and suggest that PG EDA NPs are not readily degraded in biological environments containing α ‐amylase (i.e., blood, gastrointestinal tract).…”
Section: Resultsmentioning
confidence: 99%
“…It is believed that the endosomal escape of ODN HT –PG EDA NCs is likely triggered by the proton sponge effect as the secondary amines in EDA exhibit buffering properties and possess p K a within the range of endosomal pH. [ 17 ] This hypothesis was confirmed through potentiometric titration studies, which revealed that, unlike unmodified glycogen, [ 5c,17 ] PG EDA NPs exhibit buffering capacity at pH ≈6–7, with a p K a of ≈6.4 (Figure S13, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…4A), with the adsorbed components particularly rich in serum albumin, haptoglobin, alpha-1-antitrypsin, and apolipoprotein A-II, amongst others. Radziwon, et al , 49 recently reported on cationic bovine liver glycogen-albumin hybrid constructs as pH-responsive scaffolds that can undergo endosomal escape in tumour, stromal and immune cells, whilst carrying therapeutic agents. It was observed that the hybrid nanomaterials could successfully penetrate tumour-mimicking tissues in 3D (Fig.…”
Section: Introductionmentioning
confidence: 99%